2007
DOI: 10.1653/0015-4040(2007)90[715:dtomaa]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Daily Timing of Mating and Age at Reproductive Maturity in Diaphorina citri (Hemiptera: Psyllidae)

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(100 citation statements)
references
References 16 publications
3
92
1
4
Order By: Relevance
“…It should be noted that others have reported variation in engagement in mating behavior among D. citri males, including Wenninger & Hall (2007), who found that male latency to initiate calling significantly decreased and the numbers of calls detected in 10-m bioassays significantly increased with age. Zagvazdina et al (2015) found that mean responses of D. citri males in mate-seeking bioassays decreased when barometric pressure rose or fell more than 1 standard deviation over a 24-h period.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…It should be noted that others have reported variation in engagement in mating behavior among D. citri males, including Wenninger & Hall (2007), who found that male latency to initiate calling significantly decreased and the numbers of calls detected in 10-m bioassays significantly increased with age. Zagvazdina et al (2015) found that mean responses of D. citri males in mate-seeking bioassays decreased when barometric pressure rose or fell more than 1 standard deviation over a 24-h period.…”
Section: Discussionmentioning
confidence: 89%
“…Thirty-three different males were tested during the (10 AM to 3 PM) period of greatest mating activity (Wenninger & Hall 2007). The handler placed the male onto a tree leaf using the walker tool described in Pregmon et al (2016).…”
Section: Monitoring Of Male Searching Behavior and Device Re-sponsesmentioning
confidence: 99%
“…Last instar, newly-emerged, and reproductively active females of D. citri (WENNINGER & HALL 2007), at the previtellogenic and vitellogenic stages (DOSSI & CÔNSOLI 2010), were dissected in insect saline (3 mM CaCl 2 .2H 2 O, 182 mM KCl, 46 mM NaCl, 10 mM Tris base, pH 7.2) (CSH PROTOCOLS 2007). Ovaries were immediately transferred to the proper fixative solution for further processing.…”
Section: Methodsmentioning
confidence: 99%
“…Adultos de D. citri recém-emergidos (≤ 12h) foram sexados, sendo machos e fêmeas mantidos separados em plantas de murta no interior de gaiolas de polietileno (30 cm altura x 10 cm diâmetro). Segundo Wenninger & Hall (2007), D. citri torna-se apta à cópula em torno de 2-3 dias após a emergência. Contudo, testes preliminares indicaram alta heterogeneidade quanto ao período de pré-cópula do inseto, optando-se por permitir a cópula apenas no décimo dia após a emergência.…”
Section: Methodsunclassified